Academic Achievement: It Is Not How Smart You Are, But How You Cope With Your Life And Manage Your Time (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Previous research suggests that contributing factors such as previous academic result, coping and time management can predict student success at the universities.  The purpose of this study was to investigate the relationship between previous academic grades, coping and time management practices on academic achievement among undergraduate students from four of Malaysia public institutions for higher education. 551 university students completed a Time Management Questionnaire (TMQ), COPE Inventory and provided their self-reported high school grades and current Grade Point Average (GPA).  Analysis of data from descriptive and inferential statistics was done.  Results showed that previous academic grades and the practice of time management (short range planning and attitude toward time) have no direct effect on academic achievement.  However, the use of coping strategies (problem focused and denial focused) and the practice of time management (long range planning) showed that there was a significant effect on Grade Point Average (GPA).